ANALISIS TINGKAT KECENDERUNGAN ADIKTIF PENGGUNAAN MEDIA SOSIAL PADA SISWA - Ayu Jingga Arisa; Wiryo Nuryono (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the level of social media addiction tendencies among students at Surabaya Junior High School. The study used a quantitative approach with descriptive methods. The study subjects were 89 students. The instrument used was a questionnaire with 26 statements whose validity had been tested, using a Likert scale of 1–4. Data were analyzed using descriptive statistics and categorized based on the score range. The results showed that 13% of students were in the high category, 75% in the medium category, and 11% in the low category. In general, the level of social media addiction tendencies was in the medium category. In addition, the majority of students used social media for more than 6 hours per day, indicating a potential risk of addictive behavior. These findings indicate the need for preventive efforts through increasing digital literacy, strengthening self-regulation, and mentoring from teachers and parents to ensure wiser social media use